Introduction: a rainbow feast - Quayum, Mohammad Abdul (Marshall Cavendish Editions, 2010)
This introduction examines the various aspects of short stories written by Asian and diasporic writers from different Asian societies in the English language. It also introduces the authors and stories in the collection. Furthermore, the introduction focuses on the past, present and future of literature in English in the Asian societies or among transnational Asians in the West.